Using Bathymodiolus tissue stable carbon, nitrogen and sulfur isotopes to infer biogeochemical process at a cold seep in the South China Sea. (October 2015) - Feng, Dong; Cheng, Ming; Kiel, Steffen; Qiu, Jian-Wen; Yang, Qunhui; Zhou, Huaiyang; Peng, Yongbo; Chen, Duofu
Abstract: More than 30 sites of active and inactive methane seepage have been discovered on the continental slope of the South China Sea over the past decade. Here we use stable isotopes of carbon, nitrogen and sulfur in the tissue of two bathymodiolin mussel species with different chemotrophic symbionts (methanotrophs in Bathymodiolus platifrons and sulfide-oxidizers in Bathymodiolus aduloides ) to gain insights into the biogeochemical processes at an active site in 1120 m depth on the Formosa Ridge, called Site F. Because mussels with methanotrophic symbionts acquire the isotope signature of the used methane, the average δ 13 Ctissue values of B. platifrons (−70.3‰; n =36) indicates a biogenic methane source at Site F, consistent with the measured carbon isotope signature of methane (–61.1‰ to –58.7‰) sampled 1.5 m above the mussel beds. The only small offset between the δ 13 C signatures of the ascending methane and the authigenic carbonate at site F (as low as −55.3‰) suggests only minor mixing of the pore water with marine bicarbonate, which in turn may be used as an indicator for advective rather than diffusive seepage at this site. Bathymodiolus aduloides has much higher average δ 13 Ctissue values of −34.4‰ ( n =9), indicating inorganic carbon (DIC) dissolved in epibenthic bottom water as its main carbon source. The DIC was apparently marine bicarbonate with a small contribution of 13 C-depleted carbon from locally oxidized methane. The δ 34 S values of the two mussel species indicate that they used two different sulfur sources. Bathymodiolus platifrons (average δ 34 S=+6.4±2.6‰; n =36) used seawater sulfate mixed with isotopically light re-oxidized sulfide from the sulfate-dependent anaerobic oxidation of methane (AOM), while the sulfur source of B. aduloides (δ 34 S=−8.0±3.1‰; n =9) was AOM-derived sulfide used by its symbionts. δ 15 Ntissue values differed between the mussels, with B. platifrons having a wider range of on average slightly lower values (mean=+0.5±0.7‰, n =36) than B. aduloides (mean=+1.1±0.0‰). These values are significantly lower than δ 15 N values of South China Sea deep-sea sediments (+5‰ to +6‰), indicating that the organic nitrogen is of local origin, possibly resulting from the activity of autotrophic bacteria and due to assimilation of isotopically light nitrate or ammonium by the symbionts. Highlights: B. platifrons (methanotrophic) and B. aduloides (thiotrophic) co-occur at the seep. Biogenic methane is the dominant carbon source fueling the seep system. Tissue δ 13 C of mussels are useful to assess fluid intensities at cold seeps. Tissue δ 34 S of mussels suggests complex sulfate and sulfide coupling at cold seeps.